Using Sonic Tomography to Assess the Relationship Between Internal Wood Decay and Saproxylic Beetle Communities - Vergara-Egert, P; Fierro-Tapia, C; Alaniz-Baeza, A; Carvajal-Leon, M (Elsevier B.V., 2022)
Although wood-inhabiting beetle species are known to contribute to the progressive degradation of wood by building larval galleries and dispersing fungal propagules, the relationship between decaying wood and beetle communities is difficult to be assessed. The ecological properties of trees, such as their mortality status and species, could modify the relationships between beetle communities and decaying wood. We used recently developed techniques of sonic tomography for the first time to address how the trophic structure of beetle communities varies with the internal wood decay. We developed a paired design where sonic tomograms taken in the trunk sections of live and dead trees of the Patagonian forest were related with beetles sampled with emergence traps. Beetles captured in the trunks of live trees responded weakly to the internal wood decay. Indeed, the diversity of predators in live trees was likely influenced by bark microhabitats. Conversely, most of the guild assemblages in the trunks of dead trees were impoverished as wood decay was more advanced, possibly due to decreasing microhabitat quality. Our preliminary study suggests sonic tomography offers the opportunity to distinguish how beetles modulate decaying wood, but also provides insights about the assessment of live trees with tomograms. © 2022 The Author(s)